High-velocity blueshifted Fe II absorption in the dwarf star-forming galaxy PHL 293B: evidence for a wind driven supershell? - Terlevich, Roberto (2014)
X-shooter and WHT-ISIS spectra of the star-forming galaxy PHL 293B also known as A2228- 00 and SDSS J223036.79-000636.9 are presented in this paper. We find broad (FWHM = 1000 km s-1) and very broad (FWZI = 4000 km s-1) components in the Balmer lines, narrow absorption components in the Balmer series blueshifted by 800 km s-1, previously undetected Fe II multiplet (42) absorptions also blueshifted by 800 km s-1, IR CaII triplet stellar absorptions consistent with [Fe/H] < -2.0 and no broad components or blueshifted absorptions in the He I lines. Based on historical records, we found no optical variability at the 5s level of 0.02 mag between 2005 and 2013 and no optical variability at the level of 0.1 mag for the past 24 yr. The lack of variability rules out transient phenomena like luminous blue variables or Type IIn supernovae as the origin of the blueshifted absorptions of HI and Fe II. The evidence points to either a young and dense expanding supershell or a stationary cooling wind, in both cases driven by the young cluster wind.